Structural Effect of Well-Graded Coal Bottom Ash in Improving Mechanical and Thermal Properties of Normal Concrete - Beddu S.; Basri N.A.N.; Kamal N.M.; Mohamad D.; Sukhvinder P.; Zailani W.W.A. (Springer Science and Business Media Deutschland GmbH, 2024)
Concrete is one of the most widely and worlds oldest used construction materials, due to its versatility, durability, sustainability, and economy. This study presents the way of improving normal coal bottom ash to well-graded coal bottom ash and to investigate the effects of workability, mechanical properties, and thermal properties of normal concrete when partially replaced with well-graded coal bottom ash with sand. It was observed that the workability of the concrete showed a slight increase with normal concrete containing well-graded coal bottom ash. The compressive strength of well-graded coal bottom ash achieved the designed mix design which was 40Mpa at the ages of 3, 7, and 28days compared to controlled concrete. The thermal conductivity of well-graded coal bottom ash concrete showed a decrease in value compared to controlled concrete. This research concluded that 80% of well-graded coal bottom ash concrete was the optimum percentage replacement which will help achieve the beneficial strength development. 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.